2,4,6-Tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine as a New Recyclable Hypervalent Iodine(III) Reagent for Chlorination and Oxidation Reactions - Thorat, Prerana B.; Bhong, Bhagyashree Y.; Karade, Nandkishor N. (Synlett, 2013)
The synthesis of 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine, as a new recyclable nonpolymeric analogue of (dichloroiodo)benzene, is achieved in two steps using 2,4,6-trichloro-1,3,5-triazine and 4-iodophenol. The application of 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine for the chlorination reaction of various activated arenes, olefin, and 1,3-diketone is demonstrated. The reagent 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine can be applied also for the oxidative synthesis of 1,3,4-oxadiazoles and 1,2,4-thiadiazoles under mild conditions in excellent yields. The recyclability of the 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine was possible owing to the facile recovery and reuse of the coproduced 2,4,6-tris(4-iodophenoxy)-1,3,5-triazine from the reaction mixture due to its practical insolubility in methanol.
Keywords: oxidation; hypervalent iodine reagent; (dichloroiodo)benzene; 1,3,5-triazine; chlorination